Importancia de reformar la ley de comercio electrónico, firmas, mensajes de datos y derechos al consumidor en el ecuador - Japón Romero, Carlos Edgar (2016)
The present research “IMPORTANCE OF REFORMIG THE LAW OF ELECTRONIC COMERCE, SIGNATURES, DATA MESSAGES AND CONSUMER RIGHTS IN ECUADOR”, is structured and developed according to the regulations of Academic System. The general aim of the research was guided: - Analyze the importance of the use of electronic commerce and consumer rights The descriptive method in the collection, tabulation, interpretation and analysis of results with pre-established goal was used in this work. Besides the hypothetical deductive method is used, through which the conclusions will be reached through the demonstration and verification of the hypothesis. As for the techniques to be used is the statistical sampling that a representative sample of the population is employed. Research subjects will be citizens living in the city of Loja. Resorting to be used a survey containing questions and answers to research regarding the issue. By the results of the survey we will proceed to draw conclusions and subsequent recommendations on the importance of electronic commerce and consumer rights in Ecuador.